Impact of medical fitness to drive policies in preventing property damage, injury, and death from motor vehicle collisions in Ontario, Canada. (December 2020) - Ma, Tracey; Chee, Justin N.; Hanna, Joshua; Al Jenabi, Nadia; Ilari, Frances; Redelmeier, Donald A.; Elzohairy, Yoassry
Highlights: Evaluates the road safety impact of Ontario's medical fitness-to-drive policies. Road safety losses were not incurred while medical cases were reviewed (2005–2014). The intervention prevented an estimated 1, 211 (95% CI: 780–1, 730) collisions. Interventional effect of the medical review program differed by medical condition. Abstract: Introduction: Drivers with medical conditions and functional impairments are at increased collision risk. A challenge lies in identifying the point at which such risk becomes unacceptable to society and requires mitigating measures. This study models the road safety impact of medical fitness-to-drive policy in Ontario. Method: Using data from 2005 to 2014, we estimated the losses to road safety incurred during the time medically-at-risk drivers were under review, as well as the savings to road safety accrued as a result of licensing decisions made after the review process. Results: While under review, drivers with medical conditions had an age- and sex-standardized collision rate no different from the general driver population, suggesting no road safety losses occurred (RR = 1.02; 95% CI: 0.93–1.12). Licensing decisions were estimated to have subsequently prevented 1, 211 (95% CI: 780–1, 730) collisions, indicating net road safety savings resulting from medical fitness to drive policies. However, more collisions occurred than were prevented for drivers with musculoskeletal disorders, sleep apnea, and diabetes. We theorize on these findings and discuss its multiple implications. Conclusions: Minimizing the impact of medical conditions on collision occurrence requires robust policies that balance fairness and safety. It is dependent on efforts by academic researchers (who study fitness to drive); policymakers (who set driver medical standards); licensing authorities (who make licensing decisions under such standards); and clinicians (who counsel patients on their driving risk and liaise with licensing authorities). Practical Applications: Further efforts are needed to improve understanding of the effects of medical conditions on collision risk, especially for the identified conditions and combinations of conditions. Results reinforce the value of optimizing the processes by which information is solicited from physicians in order to better assess the functional impact of drivers' medical conditions on driving and to take suitable licensing action.